24S-hydroxycholesterol: cellular effects and variations in brain diseases - Sodero, Alejandro O. (2020)
Fil: Sodero, Alejandro O. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina